Identifying Risks in Management of Educational Institutions: A Case in a Legal Entity Higher Education Institution - Taman, Abdullah; Prasojo, Lantip Diat; Yuliana, Lia; Purwanto, Nurtanio Agus (Jurnal Prima Edukasia, 2024)
Higher education is a legal entity that represents the government to serve society optimally. This research aims to identify, understand and manage risks that can hinder the achievement of organizational goals in terms of organizing higher education. This study uses a quantitative approach with a descriptive type. Research subjects were taken from leaders and employees in the Directorate of Planning and Finance, Directorate of General Affairs, Resources and Law. Directorate of Research and Community Service, Directorate of Cooperation, Information Systems, Innovation and Business, Quality Assurance Directorate, Internal Supervisory Unit, Vocational Faculty. Subject selection was carried out using a purposive technique using considerations of feasibility and competency related to the themes studied in this research. Data collection was carried out using questionnaires and interviews. The data that was collected was analyzed using descriptive quantitative analysis techniques. This risk register management is a document that functions to identify, understand and manage risks that can hinder the achievement of organizational goals. The structured risks are a development of the risk mapping that was prepared during the previous program. Risks that have been identified are not risks that are fixed (given). The risks referred to can change, increase, or even decrease according to the conditions faced by the organization. Communication in efforts to update risk data in risk register management is still very necessary as an effort to enrich the types and impacts of these risks on the organization.